Regenerative Potential of Mesenchymal Stromal Cells: Age-Related Changes - Flavia Bruna; David Contador; Paulette Conget; Benjamín Erranz; Claudia L. Sossa; Martha L. Arango-Rodríguez (Stem Cells International)
Preclinical and clinical studies have shown that a therapeutic effect results from mesenchymal stromal cells (MSCs) transplant. No systematic information is currently available regarding whether donor age modifies MSC regenerative potential on cutaneous wound healing. Here, we evaluate whether donor age influences this potential. Two different doses of bone marrow MSCs (BM-MSCs) from young, adult, or old mouse donors or two doses of their acellular derivatives mesenchymal stromal cells (acd-MSCs) were intradermally injected around wounds in the midline of C57BL/6 mice. Every two days, wound healing was macroscopically assessed (wound closure) and microscopically assessed (reepithelialization, dermal-epidermal junction, skin appendage regeneration, granulation tissue, leukocyte infiltration, and density dermal collagen fibers) after 12 days from MSC transplant. Significant differences in the wound closure kinetic, quality, and healing of skin regenerated were observed in lesions which received BM-MSCs from different ages or their acd-MSCs compared to lesions which received vehicle. Nevertheless, our data shows that adult’s BM-MSCs or their acd-MSCs were the most efficient for recovery of most parameters analyzed. Our data suggest that MSC efficacy was negatively affected by donor age, where the treatment with adult’s BM-MSCs or their acd-MSCs in cutaneous wound promotes a better tissue repair/regeneration. This is due to their paracrine factors secretion.